1997
DOI: 10.1515/humr.1997.10.4.421
|View full text |Cite
|
Sign up to set email alerts
|

Disgust in humor: Its appeal to adolescents

Abstract: Respondents were exposed to humorous episodes devoid ofdisgust, involving some degree ofdisgust, or involving highly disgusting events. Highly disgust· sensitive respondents were less amused by the humorous materiell, taken together, than were their less squeamish counterparts. In contrast, highly rebellious respondents tended to be more amused by these materials than were respondents exhibiting comparatively little trait rebelliousness. Pronounced gender differences in reacting to disgusting humor emerged. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 5 publications
3
15
0
1
Order By: Relevance
“…Baghurst, 1999;Smit, Nieto, Crespo, & Mitchell, 1999). Likewise, our findings that (a) women are more disgust sensitive than men, and (b) disgust sensitivity decreases with age replicate previous studies which used smaller samples and in person administration of the D-Scale (Haidt et al, 1994;Koukounas & McCabe, 1997;Oppliger & Zillmann, 1997;Quigley et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Baghurst, 1999;Smit, Nieto, Crespo, & Mitchell, 1999). Likewise, our findings that (a) women are more disgust sensitive than men, and (b) disgust sensitivity decreases with age replicate previous studies which used smaller samples and in person administration of the D-Scale (Haidt et al, 1994;Koukounas & McCabe, 1997;Oppliger & Zillmann, 1997;Quigley et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Among Western vegetarians, women greatly outnumber men (Beardsworth & Bryman, 1999;Neumark-Sztainer, Story, Resnick, & Blum, 1997;Worsley & Skrzypiec, 1998), and even nonvegetarian Western women eat considerably less meat than men as a proportion of the diet (Beardsworth & Bryman, 1999;Fraser, Welch, Luben, Bingham, & Day, 2000;Perl, Mandic, Primorac, Klapec, & Perl, 1998;Richardson, Shepherd, & Elliman, 1993). Correspondingly, in the US, Japan, Indonesia, and the Netherlands women and girls exhibit lower thresholds for the elicitation of disgust (Druschel & Sherman, 1999;Haidt et al, 1994;Koukounas & McCabe, 1997;Oppliger & Zillmann, 1997;Quigley, Sherman, & Sherman, 1997; first author's field notes; J. Haidt personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…We here draw on amusement and disgust because these two emotional states are often used as representatives of positive and negative emotions (Davidson, Ekman, Saron, Senulis, & Friesen, 1990;Demaree, Schmeichel, Robinson, & Everhart, 2004) and because they naturally co-occur in everyday life (Hemenover & Schimmack, 2007;Oppliger & Zillmann, 1997). Given that different emotion elicitation paradigms may impose different information processing demands that can significantly influence the physiological emotion response, we here focus on emotion elicitation through passive perception of pictures, sounds, or film clips.…”
Section: Physiological Effects Of Pure Emotionsmentioning
confidence: 99%
“…Second, we studied a mixed emotional state of amusement and disgust because prior research has demonstrated reliable co-occurrence of this pair of emotions (Hemenover & Schimmack, 2007;Oppliger & Zillmann, 1997) and extensively studied the psychophysiology of the constituent emotions (Britton et al, 2006;Demaree et al, 2004), often as representatives for positive and negative emotions (Davidson et al, 1990). Still, future research will need to address whether inferences drawn from the herestudied mixed emotional state generalize to other forms of both different-and same-valence mixed emotions (Harter & Buddin, 1987).…”
mentioning
confidence: 99%
“…Whilst fit and surprise were positively related to preference, cruelty (‘How vicious or cruel is the emotional tone of the joke towards an individual or group?’) was negatively related to preference. Other studies about sick humour showed that subjects who prefer such humour are more likely to be male (Herzog and Anderson 2000; Herzog and Karafa 1998; Oppliger and Zillmann 1997), more likely to be rebellious (Oppliger and Zillmann 1997) and are more capable to treat sick humour as playful fiction (Mindess et al 1985). …”
Section: Introductionmentioning
confidence: 99%